Da legitimidade à contradição: diferentes sentidos de escola presentes nos espaços enunciativos informatizados - Alflen, Schirley (2020)
This work aims to understand the different meaning effects produced by the pair School / Education, in statements such as “Schools kill learning”, and “The School is ours”, produced in different enunciative and discursive contexts. We firstly analyze statements by Murilo Gun, a youtuber, author of a video that circulates under the title "Schools kill learning". Before circulating on YouTube, this video initially circulated in another computerized enunciative space, TEDx, in 2016. The second statement, “The School is ours”, circulated in São Paulo high schools, in the same year, as the banner of the student movement. The theoretical device of Pecheuxtian Discourse Analysis, a theory that lies between psychoanalysis, historical materialism and linguistics, supports this process of analysis and understanding of different meaning effects, according to different norms and discursive determinations. I seek to identify, analyzing the socio-historical, political and ideological conditions that support these words, to undo the evidence and return the opacity to the statements in their contradiction. During the research, I am going to rely on the notions of subject, discourse, utterance and, according to Gallo (2015), on the notion of discourse of writing and discursive process of mediatization, among others.